Toucher, regarder, préserver la cire et le plomb. Autour du scellement pratiqué dans l’environnement des comtes de Toulouse (xiie-xiiie siècle) - Laurent Macé (Bulletin du Centre d’Études Médiévales d’Auxerre)
By taking as a subject of study the sigillary practices of the last counts of Toulouse belonging to the raimondine dynasty (1148-1249), the subject aims to show the interrelation established between the announcements of sealing and the manifestations of the princely authority that this induces. Even if the task of the impression in wax or lead of the count’s mark is supervised by specialists in corroboration, the imprint is a material projection sought by the various parties concerned by the validation of the acts of the practice. This performativity largely explains why the object printed in wax or lead is analyzed, touched, evaluated when the question of the renewal of a privilege arises. This interaction is also produced when the count’s mark comes to sanction collective decisions or when a third party requires the use of a prestigious matrix, a privilege enjoyed b those who gravitate in the proximity of the prince.